Selective Policy Imigrasi Indonesia terhadap Orang Asing dari Negara Calling Visa - Junior Perdana Sande (Indonesian Perspective, 2020)
This article aims to analyze the selective policy adopted by Indonesian immigration towards foreigners from calling visa countries. Through a qualitative research method with a descriptive analysis approach and the framework of concept of foreign policy decision making and national interests, it can be explained how the implementation of Indonesian immigration selective policy and the determination of vulnerable countries so they can be categorized in to calling visa countries. The author also seeks to provide an analysis of the anomalies in determining countries that are categorized as calling visa countries. The application of selective policy applied by the Indonesian government through the issuance of visiting permits, supervision, and immigration administrative actions against any foreigner. It is implemented more stringently and through a multi-layered process towards foreigners from calling visa countries.